Analysis of Satisfaction from Agrotourism Visitors at the Strawberry Gardens of Magelang Regency - Saputra, Yanuarius Ongky; Nuswantara, Bayu (Department of Agribusiness, Halu Oleo University, 2021)
This research is motivated by the existence and sustainability of agrotourism, so it is necessary to maintain an increase in tourist visits by continuously maintaining the quality of tourism objects so that visitor satisfaction continues to increase or at least does not experience a decrease in the end satisfaction of the strawberry bites. This effort will be achieved if the manager pays attention to the marketing mix which includes the following attributes: price according to quality, price compared to competitors, price according to benefits, price list. The product is a tangible offering from the company to the market which includes the form of packaging, quality, size, product guarantee. promotion (promotion) are all activities carried out by the company to communicate and promote its products to the target market including advertisements (banners, brochures, Facebook, Instagram) sales promotions (special discounts, product samples, free packing) location (place) is a place that used to carry out various company activities to make products and can be obtained for target customers, namely by providing strategic locations, structuring places. This research uses descriptive quantitative research with survey techniques. The sampling technique in this study uses purposive sampling. The number of respondents taken in this study was 50 respondents. the results of calculations using the method customer satisfaction index (CSI), it can be seen that the CSI value is 81.02%. And the method importance-performance analysis (IPA), is known as the attribute that needs to be improved performance in order to increase customer satisfaction. The results are based on the price/competitor attribute (price compared to competitors) with an average value of 3.78 used in this study